THE INFLUENCE OF BODY SHAMING ON ANXIETY LEVELS IN ADOLESCENTS - Silviatul Amalia; Nita Indah Lestari (LLDIKTI Wilayah X, 2025)
Technological advancement and globalization have shaped a narrowing standard that society considersgood. This creates social pressure on women, as not meeting beauty standards often leads to issues suchas body shaming. The five Asian countries with the highest prevalence of bullying are Cambodia,Vietnam, Nepal, Pakistan, and Indonesia. Indonesia ranks first with 84% of bullying cases in schools.Forty-one percent of students in Indonesia are victims of harassment, and 22% experience teasing frompeers. Body shaming impacts physical, psychological, and social aspects. It is essential to avoid factorssuch as anxiety because extreme conditions caused by body shaming can lead victims to engage indangerous behaviors like running away, self-harm, or suicide. Objective: to determine the impact of bodyshaming on anxiety levels in adolescents. Method: quantitative research with a cross-sectional design,using a total sampling technique with 50 samples. Analysis using Chi-Square. Results: The Chi-Squaretest for anxiety with body shaming showed a p-value of 0.001 and an alpha of 13.461. Therefore, it can beconcluded that H0 is rejected and Ha is accepted. So, there is a relationship between anxiety and bodyshaming.